Supply Risk Mitigation in a Decentralized Supply Chain: Pricing Postponement or Payment Postponement? - Geng, Xin; Guo, Xiaomeng; Xiao, Guang; Yang, Nan (Manufacturing and Service Operations Management, 2024)
Problem definition: In a multistage model of a bilateral supply chain, we study two postponement strategies that the downstream retailer may adopt to mitigate the supply yield risk originating from the upstream production process. The retailer could either postpone the procurement payment until after the yield is realized and pay only for the delivered amount; postpone the pricing decision to better utilize the available supply; or do both. Although both strategies have been separately studied in literature, there is little research on their combined effect and system-wide implications in a decentralized setting. Methodology/results: Taking a game-theoretic approach, we formulate a Stackelberg game and solve for the equilibrium in four scenarios, respectively, in which the retailer uses different combinations of the postponement strategies. There are three main findings. First, when the production cost is low and the yield loss is highly likely, the retailer never strictly benefits from either postponement strategy; with relatively high production cost, the retailer is more likely to adopt payment, rather than pricing, postponement. Second, we uncover a situation where postponing payment and postponing pricing are strategic complements for the retailer. That is, the use of one strategy may increase the benefit of using the other. Third, we identify conditions under which the postponement strategies can be Pareto optimal to the entire supply chain, making the firms’ profits and the consumer surplus simultaneously higher. Managerial implications: These results can be applied in many practical settings to provide guidance for firms to better design the procurement contract and properly use marketing instrument (pricing) to effectively mitigate supply risk and increase profit. Funding: G. Xiao acknowledges financial support from the Research Grants Council of Hong Kong [General Research Fund Grant PolyU 15503920]. X. Guo acknowledges the support from the National Natural Science Foundation of China [Grant 72293564/72293560]. Supplemental Material: The online appendix is available at https://doi.org/10.1287/msom.2022.0198 .